FDI inflows to Kenya: A Qualitative Case Study Approach - Contractor, Hemanshu Nitinchandra (2010)
Kenya had a long top-notch position in terms of economic development and industrialization in the region. This was due to Kenya's position as a regional hub and a prime destination for Multinational Corporations (MNCs) seeking to capture the Eastern and South African market in the 1970s. However, for the past two decades Kenya has not only experienced a significant drop in Foreign Direct Investment (FDI) inflow but a trend of well established MNCs "moving out". In contrast, FDI inflows to Uganda and Tanzania have surged over the same period. Despite various reforms in terms of liberal policy frameworks and competitive incentive packages Kenya has failed to regain its position as a regional hub. Therefore, this study was designed to conduct comparative analysis of the trends and determinants of FDI into Kenya, Uganda and Tanzania using various traditional and non-traditional variables. Data for this study was collected from three important sectors of the economy upon conducting five in-depth interviews with top management position holders in large well -established MNCs in Kenya. A qualitative case study approach was used to "lift the veils" and "dig deeper" and close up into phenomena under study. Some major findings derived from this study include firstly, corruption, political instability, governance and image of Kenya are severe obstacles to FDI inflow to Kenya. Secondly, factors such as labor quality, geographical location of Kenya and large mature market are attractive to FDI inflow into Kenya. Thirdly the government of Kenya has failed to create awareness of opportunities available in the Kenyan market. Fourthly, while MNCs from the western world are moving out, MNCs from Africa, Asia and Middle East are making entry into the market. Finally, a significant number of MNCs and companies located in Kenya account for FDI inflow to Uganda and Tanzania due to hefty transport costs. Given these findings the recommendation suggests a procedure on how Kenya can regain its attractiveness to foreign investors.